Strain elastography imaging for early detection and prediction of tumor response to concurrent chemo-radiotherapy in locally advanced cervical cancer: feasibility study - Xu, Yan (BMC Cancer, 2017)
BACKGROUND: To investigate the feasibility of strain elastography imaging in early detecting and predicting treatment response in patients receiving concurrent chemo-radiotherapy (CCRT) for locally advanced cervical cancer. METHODS: Between January 2015 and June 2016, 47 patients with locally advanced cervical cancer were enrolled in a feasibility study approved by the institutional review board. All patients underwent CCRT and received strain elastography examinations at 4 time points: pre-therapy (baseline), 1 week and 2 weeks during, as well as immediately post CCRT. Treatment response was evaluated by MRI at the time of diagnosis and immediately after CCRT. Based on the MRI findings, the treatment outcome was characterized as complete response (CR), partial response (PR), stable disease (SD) and progressive disease (PD). Strain ratio of the normal parametrial tissue vs. cervical tumor was calculated and compared with the clinical outcome. RESULTS: Out of the 47 patients, 36 patients who completed all 4 examinations were included in the analyses: 25 were classified as CR, 11 as PR, and 0 in the SD/PD groups. Strain ratios were significantly different among the time points in both the CR group (F = 87.004, p < 0.001) and PR group (F = 38.317, p < 0.001). Strain ratios were significantly difference between the CR and PR groups (F = 7.203 p = 0.011). Strain ratios between the CR group and PR group were significantly different at 1 week after treatment initiation (p < 0.05). Compared to the baseline, a significant decrease in the CR group was observed at week 1, week 2 and post treatment (all p < 0.001), while a significant decrease in the PR group was shown in week 2 and post treatment (both p < 0.05), but not at week 1 during CCRT (p = 0.084). CONCLUSIONS: We have conducted a prospective longitudinal study to evaluate tumor response in women receiving CCRT for cervical cancers. This study has demonstrated the potential of strain elastography imaging in monitoring and early predicting tumor response induced by CCRT. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12885-017-3411-5) contains supplementary material, which is available to authorized users.